Experimental modal analysis of a cross-laminated timber slab. (2022) - Kawrza, M.; Furtmüller, T.; Adam, C.; Maderebner, R.
Abstract: This paper presents the results of an investigation of the dynamic response of a point-supported cross-laminated timber (CLT) slab without joists with a column grid of 5.0 × 5.0 m and overall dimensions of 16.0 × 11.0 × 0.2 m. The results are based on a detailed experimental modal analysis, identifying seven modes from the dynamic response of 651 measurement points, including natural frequencies, mode shapes and damping ratios. These modal parameters exhibit a time variance that is due to environmental influences during the measurement period of two days. As a result of this disturbance effect, the determined mode shapes have a non-negligible imaginary part, which is eliminated by correcting each of the 73 measurements individually. The findings presented provide in-depth insight into the dynamic behavior of the large-scale CLT structure with point supports realized with a novel steel connector.